2021
DOI: 10.5295/cdg.201262mm
|View full text |Cite
|
Sign up to set email alerts
|

The assurance of sustainability reports and their impact on stock market prices

Abstract: The publication of non-financial information is a trend in recent decades in listed companies. From this fact, the need arises to provide credibility to the information by verifying an independent professional who provides a guarantee of the published information. Therefore, this article analyses whether the verification of sustainability reports influences the stock prices of Ibex-35 companies. With this aim, a content analysis has been prepared that allows us to quantify aspects as relevant as the commission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 74 publications
3
15
0
3
Order By: Relevance
“…The study findings showed that investors favour companies that adopt external assurance and that they prefer assurance statements to be broad in scope, to offer a reasonably high level of assurance and to be of good general quality. Miralles-Quir os et al (2021), in their study of Spanish companies listed on the Ibex-35 index, considered whether the adoption of assurance influenced stock prices. The main conclusions drawn were that these companies are increasingly socially committed and seek to transfer assured information to their stakeholders, a goal that is approved by investors, in line with the level of assurance obtained.…”
Section: External Assurancementioning
confidence: 99%
“…The study findings showed that investors favour companies that adopt external assurance and that they prefer assurance statements to be broad in scope, to offer a reasonably high level of assurance and to be of good general quality. Miralles-Quir os et al (2021), in their study of Spanish companies listed on the Ibex-35 index, considered whether the adoption of assurance influenced stock prices. The main conclusions drawn were that these companies are increasingly socially committed and seek to transfer assured information to their stakeholders, a goal that is approved by investors, in line with the level of assurance obtained.…”
Section: External Assurancementioning
confidence: 99%
“…The application of this directive has opened a debate on whether or not companies do in fact comply with it and what the objective of this compliance is ( Caputo and Pizzi, 2019 ; Dumay et al., 2019 ). In addition, several investigations have shown the importance of disclosing non-financial information for companies, not only due to complying with this directive, but also as a sign of a commitment to society ( Navarro et al., 2010 ; Gamerschlag et al., 2011 ; Dhaliwal et al., 2012 ; Miralles-Quirós et al., 2021 ) and as a mechanism to reduce information asymmetries that occur in markets (Signal Theory) ( Cheng et al., 2014 ; Saitua, 2015 ; Romito and Vurro, 2021 ). Disclosure helps the investor to understand the management of the company and know how these policies can affect their investments ( Gershoni and Low, 2021 ; Martín et al., 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies are mainly divided into two categories. The first kind of research focuses on the relationship between CSR reporting and company characteristics, such as the relationship between ESG reporting or CSR practice and financial performance [23,24], the association between voluntary CSR reporting and financial statement auditing [25], the heterogeneous links between board gender diversity and corporate social performance [26], the effect of the internal side of social responsibility on the firm competitive success [27], how the assurance of sustainability reports affect stock market price [28], etc. The second kind of research focuses on CSR reporting, e.g., the analysis on the content of China's sustainability report [29], a summary of the requirements of the CSR reporting in China [12], and identifying whether the CSR reports are symbolic or substantive [30], exploring of the main drivers of CSR and CSR reporting of large Chinese listed companies [31], comparing of the form and content of CSR reports between Chinese multinational corporations and their Western counterparts [32], evaluating the quality of CSR reports through a comparative analysis of Chinese state-owned and private real estate companies [33], and so on.…”
Section: Literature Reviewmentioning
confidence: 99%